Juvenile Delinquency Problems in “Pumped up Kicks” Song's Lyrics - Salsabila, Shifa; Elis Fitriani; Cindya Risma Oktafia; Khoiriyatun Nisa’; Salsa Maya Adelia; Windy Ikaluny (Media Antartika Indonesia, 2023)
Social issues often happen in everyone’s life. Not only happened in the movies, but it also happened in our real life. Some people tell it through lyrics and make it into a song, just like the problems researchers have found in the lyrics of the ‘Pumped up Kicks’ song. This study aims to address one of the social issues, namely juvenile delinquency, in the lyrics of the “Pumped up Kicks” song. The method used to analyze the juvenile delinquency in